PENDIDIKAN ISLAM SEBAGAI INSTRUMEN KULTURAL DAN POLITIK - Yamin, Ashabul; Nurbaya, Siti (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2024)
This article aims to examine the cultural and political roles in Islamic education. The research adopts a library research approach by reviewing various sources such as books, journals, theses, and other publications. Data collection is conducted through document analysis, with data sources obtained from the internet, Google Scholar, and Google Browser. The data analysis in this article refers to the method proposed by Miles and Huberman. The results of the study show that: 1) The cultural functions of Islamic education include: a) Preservation of Islamic culture, b) Enhancement of Islamic literacy, c) Development of religious character. 2) The political functions of Islamic education include: a) Producing leaders with Islamic character, b) Shaping Islamic political awareness, c) Inspiring Islamic governance systems, d) Encouraging political participation, e) Enhancing accountability in governance.